CONSUMER PREFERENCE OF SKINCARE PRODUCT USING ANALYTICAL HIERARCHY PROCESS (AHP) - Elisa Suhadi; Joy Elly Tulung; Emilia Margareth Gunawan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
According to Indonesia’s Digital Marketing Association, Wardah, Nature Republic, Innisfree product are on the top 3 best beauty product in Indonesia. Brand ambassador, brand image, country of origin, online review and product packaging are some factors that can influence consumer preference in choosing a product or services. This research aims to know which criteria is most important for customer in selecting beauty brand and to know the most preferable beauty brand in Manado. This research used analytical hierarchy process with total sample 60 respondents which are citizen in Manado. The result shows that there are top three criteria that has the most influence for consumer preference of beauty brand product which are brand image, price, and online review. The rest criteria that are brand ambassador, country of origin and product packaging are not the main things that influence the consumers. Every beauty brand company need to pay attention seriously toward these factors. The result also shows that Wardah become the most preferable beauty brand by the consumer, followed by Nature Republic, and Innisfree in the last place. Innisfree should improve their performance in every sector especially in the criteria that most influence the customers’ preference.   Keywords: marketing, consumer behavior, consumer preference